RESPON ADAPTIF KUMBANG LEMBING PEMAKAN D AUN Henospilachna vigintioctopunctata (Fabricius) (COLEOPTERA: COCCINELLIDAE: EPILACHNINAE) DAN TUMBUHANINANGNYA TERHADAP MUSIM KEMARAU DIDAERAH BERIKLIM TROPIS KERING PASURUAN DAN MALANG - JAWATIMUR - Sih Kahono (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Adaptive responses of an herbivorous ladybird beetle Henosepilachna vigintioctopunctata (Epilachninae) and the host plants to dry season were studied in Pasuruan and Malang, East Java. Nineteen species of host plants of the beetle have been recorded in Java, however only fiveteen species are found as preferred host plants of the beetles in Pasuruan and Malang. During the season beetles tend to prefer the plants of Datura metel, Brugmansia spp., Solanum melongena, S. torvum, S. pseudocapsicum, and 5. nigrum as their hosts and this might course strong damage to the plants.It is obvious that the beetles tend to move to the humid places to find more suitable food. It is also found that during the days of drought, the beetles feed on eggplant fruits by tunnelling into the flash of the fruits.Some of the beetles ovaries would not develop in the drought and a part of them might enter the diapause stage.Other responses of the beetles to drought will be discussed in the paper.